Komparasi Edukatif antara Novel Bumi Manusia Karya Pramoedya Ananta Toer dan Teruslah Bodoh Jangan Pintar Karya Tere Liye - Afifah, A. Rifka; Saleh, Muhammad; Asri, Aswati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to describe the comparative educational dimensions in Pramoedya Ananta Toer's Bumi Manusia novels and Tere Liye's Teruslah Bodoh Jangan Pintar (Continue to Be Stupid, Don't Be Smart) through the perspective of Hans Robert Jauss's literary reception theory. Using a qualitative descriptive method with a comparative literature approach, this study examines three main dimensions: affective, cognitive, and moral. The data sources are linguistic units in both novels collected through literature study, reading and note-taking, and content analysis. Data analysis was conducted systematically through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that both novels function as media for social transformation and character education. Bumi Manusia novel presents colonial resistance through a poetic-symbolic style, while Tere Liye's work critiques modern capitalism straightforwardly. The novelty of this study lies in the application of a three-dimensional educational analysis, the first of its kind in Teruslah Bodoh Jangan Pintar (Continue to Be Stupid, Don't Be Smart), emphasizing literature's position as a relevant, cross-era humanistic educational tool.